1985
DOI: 10.1021/ac00289a026
|View full text |Cite
|
Sign up to set email alerts
|

Stereoisomer differentiation of 2-acetamido-2-deoxyhexose by mass spectrometric measurement of relative gas-phase alkali ion affinities

Abstract: Catlonlzed dlmers [hexosamlne-cat-matrlx]'of 2-acetamldo-2-deoxy-~glucose, 2-acetamldo-2-deoxy-~-mannose, and 2-acetamldo-2deoxy~alactose were generated by fast atom bombardment (FAB) uslng different alkall catlons and glycerol, S-valerolactame, and diethanolamine matrlces. From thelr unimolecular decomposltlon (metastable Ions) malnly two klnds of Ions are observed resultlng from the retention of the cation either by the amino sugar (Ion a) orland by the matrlx (Ion b). For a given hexosamlne their relatlve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In most cases, equilibrium 1 could be attained from both sides, and the AG' changes reported in Table 1 The Kinetic Method. The limitations of the equilibrium method have suggested extension to nitronium ion-bound dimers of the kinetic method developed by Cooks and coworkers (35,36) for proton-bound dimers and subsequently applied to alkali cation-bound dimers (37) and other metal cation-bound clusters (38)(39)(40)(41). It is a limiting procedure, based on several nonrigorous assumptions that nevertheless has proved highly successful in a var-iety of applications, especially in those systems where weakly bound dimers undergo simple dissociation kinetics, which is the case of many nitronium ion-bound dimers (see below).…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, equilibrium 1 could be attained from both sides, and the AG' changes reported in Table 1 The Kinetic Method. The limitations of the equilibrium method have suggested extension to nitronium ion-bound dimers of the kinetic method developed by Cooks and coworkers (35,36) for proton-bound dimers and subsequently applied to alkali cation-bound dimers (37) and other metal cation-bound clusters (38)(39)(40)(41). It is a limiting procedure, based on several nonrigorous assumptions that nevertheless has proved highly successful in a var-iety of applications, especially in those systems where weakly bound dimers undergo simple dissociation kinetics, which is the case of many nitronium ion-bound dimers (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Carbohydrates constitute one of the most important classes of biomolecules and N ‐acetylhexosamines in particular form important constituents of antibiotics such as aminoglycosides,1 biological polymers such as glycoproteins,2 and lipopolysaccharides,3 which possess immunological activities. Several groups have reported structural elucidation of isomeric monosaccharides by mass spectrometry 4–18. During our earlier study of hydrogen‐bonding interactions of lysine with mono‐ and disaccharides under ESI conditions19 we observed that lysine forms abundant proton‐bound heterodimers with N ‐acetylhexosamines under electrospray ionization (ESI) conditions.…”
Section: Relative Abundance Ratio (A/b) [N‐acetylhexosamine+h]+ (A) Amentioning
confidence: 99%
“…In response to this possibility, special measures have sometimes been taken; for example, Chen and Miller have used a high-pressure FAB source to generate thermalized cluster ions by collisional cooling (45,46). FAB has also proven extremely useful in generating dimer ions of nonvolatile species, and alkali metal ions as well as protons have been used as the binding species (47)(48)(49); (also see Section VB). Desorption chemical ionization (DCI) is another particularly useful method for ionizing less volatile or thermally labile compounds in kinetic method studies.…”
Section: Practical Considerationsmentioning
confidence: 99%